Factors determining early internationalization of entrepreneurial SMEs: Theoretical approach - Agne Matiusinaite; Jurgita Sekliuckiene (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2015)
Purpose - This study extends the scientific discussion of early internationalization of SMEs. The main purpose of this paper - to develop a theoretical framework to investigate factors determining early internationalization of international new ventures. Design/methodology/approach - The conceptual framework is built on the analysis and synthesis of scientific literature. Findings - This paper presents different factors, which determine early internationalization of international new ventures. These factors are divided to entrepreneurial, organizational and contextual factors. We argue that early internationalization of international new ventures is defined by entrepreneurial characteristics and previous experience of the entrepreneur, opportunities recognition and exploitation, risk tolerance, specific of the organization, involvement into networks and contextual factors. Study proved that only interaction between factors and categories has an effect for business development and successful implementation of early internationalization. Research limitations/implications - The research was conducted on the theoretical basis of scientific literature. The future studies could include a practical confirmation or denial of such allocation of factors. Originality/value - The originality of this study lies in the finding that factor itself has limited effect to early internationalization. Only the interoperability of categories and factors gives a positive impact on early internationalization of entrepreneurial SMEs.
Keywords: F23; M16; L26; 330; early internationalization; international new ventures; entrepreneurial; organizational and contextual factors